Decisions about Postsecondary Education, their Returns in Colombia (2014)
This study analyzes the economic returns to schooling decisions made by high school graduates in Colombia. We wanted to verify if the economic returns (wages) obtained by new postsecondary education graduates compensate for the economic and psychological investment they made to get that academic degree. To answer that question, we estimated these economic returns for each type of postsecondary degree available in Colombia (technical education, technological education, undergraduate studies, graduate studies) by origin of the institution (public or private). Our methodological strategy includes the generation of a micro-database that contains agents’ socio-economic backgrounds and also their individual labor market outcomes. Because agents with very similar characteristics and the same schooling decisions might obtain different economic returnsfrom education, we considered as part of our empirical strategy the inclusion of an approximation of agents’ cognitive abilities.